Pediatric emergency medicine - McQueen, Alisa; Paik, S. Margaret (Boca Raton, FL : CRC Press, 2019)
This book includes 200 clinical cases which present as emergencies. Congenital and acquired conditions affecting all body systems in infants and children are covered, including allergy, abuse, burns, fractures and other trauma, feeding problems, foreign bodies, genetic disorders, infections, poisoning, haematology, oncology, and much more. Cases appear in random order, reflecting actual practice in emergency medicine, and reinforcing skills in investigation, diagnosis, and treatment. It is superbly illustrated with high-quality radiographic images and photographs and is indispensable for all health professionals dealing with emergencies involving children.
OCLC-licensed vendor bibliographic record.
Keywords: Pediatric emergencies -- Case studies; MEDICAL / Emergency Medicine; MEDICAL / Pediatric Emergencies